Engineering novel S-glycosidase activity into extremo-adapted β-glucosidase by rational design - Almulhim, Nourah (2021)
Biocatalysts have proven their efficiency and superiority in industry for the last few decades. Enzymes are made by nature to carry out specific functions required by the host organisms, therefore the practical applications of enzymes can be limited to their natural functions and this has encouraged efforts in the development of these natural catalysts to work in different conditions and with a significantly broader range of substrates.